Adaptasi Sekolah terhadap Perubahan Lingkungan Eksternal: Strategi dan Implementasi - Andhika Wirawan; Fadiyah Putri Kusmana; Febriana Putri Nabilah; Hesti Kusumaningrum (Lembaga Pengembangan Kinerja Dosen, 2024)
This article discusses how schools can adapt to changes in the external environment through effective adaptation strategies and their implementation. External environment changes, including advancements in technology, dynamic education policies, and social and economic changes affect the way schools operate and deliver education. This article identifies these changes and outlines the adaptation strategies required by schools to meet these challenges. The adaptation strategies discussed include the implementation of technology, as well as professional training for teachers. In addition, the article also discusses the process of strategy implementation, which includes planning and so on. The challenges faced in the adaptation process, such as limited resources as well as funding issues, and the solutions that can be applied, are also the main focus. By providing practical guidance and solutions to challenges that may arise, this article aims to help schools effectively manage external changes and maintain relevant and responsive education quality.